Immature teratoma of the ovary: A clinicopathological study of 28 cases - Kedar K Deodhar; Pallavi Suryawanshi; Milap Shah; Bharat Rekhi; R F Chinoy (Wolters Kluwer Medknow Publications, 2011)
Aim: Immature teratoma (IT) of the ovary represents 1% of all ovarian cancers and 20% of malignant ovarian germ cell tumors. This retrospective study of 28 such cases aims to look at its morphological spectrum and to study the correlation of the grade and stage of the tumor with prognosis. Materials and Methods: A retrospective study of 28 cases of IT of the ovary was done. Neuroepithelium was graded as grade I, II and III according to the standard criteria. The presence of immature mesenchyme was also looked for and similarly graded. Results: The median age for the cases was 19 years and abdominal pain was the commonest symptom. Neuroepithelium was seen in 26 cases (6 were grade I, 13 were grade II, and 7 were grade III); and two showed immature mesenchymal tissue (IM) only. IM was seen in all 28 cases, but no correlation with the grade of the IT of the ovary is found. The follow up is available in 23 cases ranging from 6 months to 78 months (median 33 months). Of these, 13 were stage I, 3 were stage II and 7 were stage III ITs. Out of 23 patients, 17 patients were alive without evidence of disease recurrence during the last follow up. Adverse events in the form of death and local recurrence occurred in 6 patients. One patient died of the disease at 7 months duration from the disease onset (stage III, grade II IT). Conclusion: Morphological spectrum of IT of ovary is varied. Immature mesenchyme was seen in all the cases of IT of ovary and its presence should prompt a careful search for immature neuroepithelium. Stage I IT of ovary has better prognosis. Combination of surgery and chemotherapy can give longer survival even in recurrent disease.